The Relationship between Social Factors and Decision-Making to Watch Chinese Drama of Gen Z in Bangkok: ความสัมพันธ์ระหว่างปัจจัยทางสังคมกับการตัดสินใจชมละครจีนของ Generation Z ในเขตกรุงเทพมหานคร - Tosompap, Kittiyaporn; Chomngam, Pornprom (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2022)
A study of the relationship between social factors and decision-making to watch Chinese drama of Gen Z in Bangkok. The purpose of this study are 1) To study the social factors of Gen Z viewers in Bangkok 2) To study the decision-making to watch Chinese drama of Gen Z viewer in Bangkok 3) To study the relationship between social factors and decision-making to watch Chinese Drama of Gen Z in Bangkok. Samples were 129 aged between 12-24 years in Bangkok, who were viewers of Chinese drama. The study used questionnaires as a tool for data collection. The data were analyzed by multiple regression analysis. The results revealed that 1) Most of the samples emphasized the reference group of social factors due to they are invited by social media such as Twitter and Facebook to watch Chinese drama. 2) Viewers’ post-watching behavior decision to continue watching that Chinese drama until the end is the most significant factor in their decision to watch Chinese drama because Chinese drama is very fun, and the viewers are relaxed. 3) There is a significant relationship between social factors and the decision-making to watch Chinese drama of Gen Z viewers in Bangkok at 0.01 level.